2010
DOI: 10.1177/0956797610384145
|View full text |Cite
|
Sign up to set email alerts
|

Do Babies Learn From Baby Media?

Abstract: In recent years, parents in the United States and worldwide have purchased enormous numbers of videos and DVDs designed and marketed for infants, many assuming that their children would benefit from watching them. We examined how many new words 12- to 18-month-old children learned from viewing a popular DVD several times a week for 4 weeks at home. The most important result was that children who viewed the DVD did not learn any more words from their monthlong exposure to it than did a control group. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(118 citation statements)
references
References 18 publications
10
103
1
4
Order By: Relevance
“…Our results are in line with studies on word learning that have demonstrated that contingent interaction is the heart of social learning communicative processes (DeLoache et al, 2010;O'Doherty et al, 2011;Roseberry, Hirsh-Pasek, & Golinkoff, 2013). The results also agree with studies that illustrated the facilitative effects of parental guidance on the comprehension of the representational status of graphs (Gauvain, De la Ossa, & Hurtado-Ortiz, 2001;Szechter & Liben, 2004) and videos (Troseth, 2003).…”
Section: Discussionsupporting
confidence: 95%
“…Our results are in line with studies on word learning that have demonstrated that contingent interaction is the heart of social learning communicative processes (DeLoache et al, 2010;O'Doherty et al, 2011;Roseberry, Hirsh-Pasek, & Golinkoff, 2013). The results also agree with studies that illustrated the facilitative effects of parental guidance on the comprehension of the representational status of graphs (Gauvain, De la Ossa, & Hurtado-Ortiz, 2001;Szechter & Liben, 2004) and videos (Troseth, 2003).…”
Section: Discussionsupporting
confidence: 95%
“…For example, from 12 to 24 months of age, toddlers can begin to learn novel words from commercially available "word learning" videos, but only if their parents watch with them and reteach the words, essentially using the videos as a learning scaffold to build the language skills. 19,20 In one longitudinal study of low-income families, 14-month-olds whose mothers had talked with them during educational TV programming since infancy showed more advanced language development than infants whose mothers did not talk with them during media use (although this finding also may have reflected how much mothers spoke to children in general). 21 The few experimental studies showing independent learning of words from videos at this age have been limited by their low ecologic validity 22 or have shown that toddlers lose the knowledge learned over time without repetition.…”
Section: At What Age Can Infants and Toddlers Learn From Screens?mentioning
confidence: 99%
“…4 The chief factor that facilitates toddlers' learning from commercial media (starting around 15 months of age) is parents watching with them and reteaching the content. 5,6 The interactivity of touchscreens enables applications (apps) to identify when a child responds accurately and then tailor its responses, thereby supporting children at their levels of competence. Emerging evidence shows that at 24 months of age, children can learn words from live video-chatting with a responsive adult 7 or from an interactive touchscreen interface that scaffolds the child to choose the relevant answers.…”
Section: Infants and Toddlersmentioning
confidence: 99%